Utilization Virtual Laboratory in Physics Learning: Bibliometric Analysis - Dwikoranto; Widiasih (Indonesia Approach Education, 2023)
This research aims to find out the trend of the author's topics and keywords that are widely used related to Virtual Lab Physics to find out future research opportunities. The research method used is descriptive analysis method research through the bibliometric approach. The results of a Google Scholar database search found 463,000 articles for 2016-2021 with the keywords